Recent advancements in thermal performance of nano-fluids charged heat pipes used for thermal management applications: A comprehensive review. (5th November 2022) - Pathak, Sudhir Kumar; Kumar, Rajat; Goel, Varun; Pandey, A.K.; Tyagi, V.V.
Graphical abstract: Highlights: The recent advancement in thermal performance of nanofluids charged heat pipes for different thermal management applications are discussed. The recent advances in the preparation, characterization and stability enhancement methods of nanofluids. Heat transfer mechanism that contributes to the change in the thermal performance of heat pipes are summarized. Critical technical issues associated with nanofluids charged heat pipes and future recommendations for further design and development of effective heat pipes. Abstract: Heat pipes are highly effective compact heat exchanger systems used in wide areas of thermal devices. Previously, conventional working fluids have been used in heat pipes for effective heat transfer in various applications. In recent years, researchers have been looking at ways to improve heat transmission in heat pipes by employing nano-additives in base liquids known as nanofluids. Nanofluids have higher thermal performance and lower thermal resistance compared to conventional working fluids. This study aims to summarize the recent advancements in thermal performance of nanofluids charged heat pipes used for different thermal management applications. Also, this study highlights nanofluids' preparation, characterization, and stability enhancement methods. The findings of several studies found that the decrease in thermal resistance between (20–80%) is caused by the development of a porous coating on a wick surface. Also, experiments show that nanofluid-charged heat pipes perform best between a 50–70% filling ratio. Nanofluids increase heat pipes' heat transfer coefficient by 20–25% more than distilled water. Additionally, it discusses the mechanism of heat transfer that contribute to the change in thermal output of various heat pipes. The thermal efficiency of heat pipes is improved due to higher thermal conductivity and increased nucleation sites of nanofluids. The critical technical issues associated with nanofluids charged heat pipes and future recommendations are also highlighted in this study. This study will provide new insights to researchers from the scientific fraternity to understand the physics behind improving the thermal output of various nanofluids charged heat pipes compared to conventional fluids.